A prospective study on insect bite hypersensitivity in horses exported from Iceland into Switzerland. - Torsteinsdottir, Sigurbjörg; Scheidegger, Stephan; Baselgia, Silvia; Jonsdottir, Sigridur; Svansson, Vilhjalmur; Björnsdottir, Sigridur; Marti, Eliane (Acta Veterinaria Scandinavica, 2018)
Insect bite hypersensitivity (IBH) is an IgE-mediated dermatitis caused by bites of Culicoides spp., which occurs frequently in horses imported from Iceland to continental Europe. IBH does not occur in Iceland because Culicoides species that bite horses are not present. However, Simulium vittatum (S. vittatum) are found in Iceland. In Europe, blood basophils from IBH-affected horses release significantly more sulfidoleukotrienes (sLT) than those from healthy controls after in vitro stimulation with Culicoides nubeculosus (C. nubeculosus) and S. vittatum. Aims of the study were: (I) using the sLT release assay, to test if horses living in Iceland were sensitized to S. vittatum and (II) to determine in a longitudinal study in horses imported from Iceland to Switzerland whether the sLT release assay would allow to predict which horses would develop IBH.